Pemanfaataan Tepung Tape Singkong (Manihot utilissima) pada Pembuatan Kue Nastar Isi Selai Nangka - Niquita Aurellia Az Zahra; Niken Purwidiani; Lilis Sulandari; Nugrahani Astuti (STIKes Ibnu Sina Ajibarang, 2025)
This research focuses on nastar cookies filled with jackfruit jam, in which wheat flour as the main ingredient is proportionally substituted with cassava tapai flour to reduce the use of wheat flour. The aim of this study is to determine the organoleptic quality of nastar cookies with jackfruit jam filling—including color, shape, aroma, taste, and texture—as well as their nutritional content, including protein, carbohydrates, fat, ash, and moisture. This study uses an experimental method. Data collection was conducted through sensory evaluation by 30 panelists. The independent variable is the proportion of cassava tapai flour (10g, 20g, and 30g). The dependent variable is the organoleptic quality, including color, shape, aroma, taste, and texture. The controlled variables include the type of ingredients, equipment, and processing techniques. Data analysis was carried out using one-way ANOVA followed by Duncan's multiple range test. The results show that: 1) The best organoleptic quality of nastar cookies with jackfruit jam filling was found in treatment A1, which used 10 grams of cassava tapai flour. This treatment received the highest average panelist scores: color 4.00, characterized by a golden yellow appearance; shape 3.87, described as a neat half-sphere; aroma 3.40, indicating a distinctive butter scent typical of nastar, a moderate cassava tapai aroma, and a fresh scent from the jackfruit-pineapple jam; taste 3.40, characterized as sweet, savory, with a hint of cassava tapai, and a sweet-sour taste from the filling; and texture 3.87, noted as soft, crumbly, and not soggy. 2) The nutritional content with protein 8.89%, carbohydrates 59.36%, fat 7.08%, ash 1.12%, and moisture content 23.50%. This research is also expected to be an alternative for developing functional food products based on local foods that have high nutritional and economic value.